Nanometer pixel point and preparation method and application thereof

Nanopixel dots are prepared by using composite nanoparticles with core-shell structures and electrochromic conductive polymers, and through optical tweezer system assembly and electrochemical regulation, the dispersion absorption and ohmic loss problems studied in nanoscale pixels in the prior art are solved, and the optical response and multiplexed regulation effects with high efficiency and low energy consumption are achieved.

CN119799323APending Publication Date: 2025-04-11JINAN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411861518.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing nanoscale pixel research is based on precious metal plasmon materials, which has problems with dispersion absorption and ohmic loss, and the preparation process is complex, which limits its application.

Method used

Complex nanoparticles with core-shell structures, the core is an aminolated full-die nanoparticle, and the shell is an electrochromic conductive polymer. It is assembled through optical tweezers system to form nanopixel dots and is subject to multiple control through electrochemical means.

Benefits of technology

It realizes efficient Fano resonance active tuning, vivid color dynamic switching, fast refreshing speed, high contrast, low energy consumption, no thermal effect, and larger tuning amplitude, suitable for different application occasions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005193315000000011
    Figure HDA0005193315000000011
  • Figure HDA0005193315000000021
    Figure HDA0005193315000000021
  • Figure HDA0005193315000000031
    Figure HDA0005193315000000031
Patent Text Reader

Abstract

The invention discloses a nano pixel point and a preparation method and application thereof. The nano pixel point comprises a composite nanoparticle of a core-shell structure, and the core of the composite nanoparticle is an aminated all-dielectric nanoparticle; the shell of the composite nanoparticle is an electrochromic conductive polymer; and the all-dielectric nano-particles comprise at least one of silicon nano-particles, germanium nano-particles, tellurium nano-particles and gallium arsenide nano-particles. According to the invention, the nano conductive polymer coated all-dielectric nanoparticles are used as the nano pixel points for the first time, the patterned arrangement of the nano pixel points is carried out through the precise control of the optical tweezers system, and then the optical response of the nano pixel points is regulated and controlled in a multi-path manner through an electrochemical means, so that the refreshing speed is high, the contrast ratio is high, the energy consumption is low, and no heat effect exists. The prepared micro display device has potential application value in highly integrated photoelectric regulation and control, display devices or high-density information coding.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the synthesis and application fields of nano photoelectric materials, and in particular to a nano pixel point and a preparation method and application thereof. Background Art

[0002] As the basic unit used to record and display information in optoelectronic devices, the reduction of pixel size and the increase of pixel distribution density help to make the display screen have higher resolution. However, when traditional pixels are compressed to the nanoscale, the luminous intensity is limited. While improving the resolution, the brightness of the display screen will be insufficient. Therefore, it is particularly important to construct a single-molecule or single-particle-based parametric optoelectronic tunable unit of amplitude, phase, polarization, etc. at the nanoscale and then prepare nanoscale pixels. Most of the existing nanoscale pixel research is based on precious metal plasmon materials, which have obvious dispersion absorption and ohmic loss. Studies have shown that high-refractive-index all-dielectric nanomaterials can also effectively enhance the interaction between light and matter, but the refractive index change caused by electrically regulating a single-component all-dielectric material is limited. In addition, some of the reported work usually involves complex silicon-based micro-nano processing such as focused ion beams, which has a complex preparation process and high cost, limiting its application. Therefore, composite nanoscale pixels based on all-dielectric nanoparticles need to be studied, and it is still difficult to arrange pixels in a pattern and apply them to micro-display technology. Summary of the invention

[0003] In order to overcome at least one technical problem existing in the above-mentioned prior art, one of the objectives of the present invention is to provide a nano-pixel.

[0004] A second object of the present invention is to provide a method for preparing nano-pixel dots.

[0005] A third object of the present invention is to provide a micro display device.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] The first aspect of the present invention provides a nano-pixel point, which includes composite nanoparticles with a core-shell structure, wherein the core of the composite nanoparticle is an amino-treated all-dielectric nanoparticle; the shell of the composite nanoparticle is an electrochromic conductive polymer; the all-dielectric nanoparticle includes at least one of silicon nanoparticles, germanium nanoparticles, tellurium nanoparticles, and gallium arsenide nanoparticles.

[0008] Preferably, the amino-modified all-media nanoparticles are spherical or quasi-spherical.

[0009] Preferably, the electrochromic conductive polymer is selected from at least one of polyaniline, polypyrrole, polythiophene and polyacetylene.

[0010] Preferably, the diameter of the all-medium nanoparticles is 50-200 nm.

[0011] Preferably, the particle size of the nano-pixel dots is 60-250 nm.

[0012] The second aspect of the present invention provides a method for preparing the nano-pixel dots provided in the first aspect of the present invention, comprising the following steps:

[0013] The aminated all-medium nanoparticles are firstly mixed with a surfactant and an acid solution, and then mixed with a monomer of an electrochromic conductive polymer and an oxidant for reaction to obtain the nano pixel point.

[0014] Preferably, the preparation method of the aminated all-medium nanoparticles is: mixing the all-medium nanoparticles with an ammonia solution, and then mixing and reacting with γ-aminopropyltriethoxysilane. The purpose of aminated nanoparticles is to increase hydrophilicity and provide functional groups for combining with polymers.

[0015] Preferably, the method for preparing the amino-modified all-medium nanoparticles comprises the following steps:

[0016] Step (1): mixing all-medium nanoparticles with a solvent to prepare an all-medium nanoparticle dispersion;

[0017] Step (2): adding an ammonia solution dropwise into the all-medium nanoparticle dispersion and mixing the mixture to obtain a mixed solution;

[0018] Step (3): mixing the mixed solution with γ-aminopropyltriethoxysilane to react and obtain the amino-modified all-medium nanoparticles.

[0019] Preferably, in step (1), the solvent is an ethanol solution.

[0020] Preferably, in the all-media nanoparticle dispersion, the concentration of the all-media nanoparticles is 0.03-0.08 mol / L.

[0021] Preferably, in step (1), the mixing step is first ultrasonication and then magnetic stirring; further preferably, in step (1), the mixing step is first ultrasonication and then magnetic stirring for 30 to 60 minutes.

[0022] Preferably, in step (1), the concentration of aqueous ammonia is 2 to 2.7 mol / L.

[0023] Preferably, in step (2), the mixing time is 1 to 2 hours.

[0024] Preferably, the mixing reaction time in step (3) is 6 to 10 hours.

[0025] Preferably, the molar ratio of the ammonia water to the all-medium nanoparticles is (10-36):1.

[0026] Preferably, the acid solution is a hydrochloric acid solution.

[0027] Preferably, the concentration of the hydrochloric acid solution is 0.5-1.5 mol / L.

[0028] Preferably, the molar ratio of the γ-aminopropyltriethoxysilane to the all-medium nanoparticles is (3-10):1.

[0029] Preferably, the oxidizing agent is selected from ammonium persulfate and / or potassium persulfate.

[0030] Preferably, the monomer of the electrochromic conductive polymer is selected from at least one of aniline, pyrrole and thiophene.

[0031] Preferably, the surfactant is selected from dodecyl sulfonate.

[0032] Preferably, the molar ratio of the surfactant, the amino-modified all-medium nanoparticles, and the acid solution is 1:(33-200):(83-250).

[0033] Preferably, the molar ratio of the amino-modified all-dielectric nanoparticles, the monomer of the electrochromic conductive polymer, and the oxidant is (50-200):1:(0.5-3).

[0034] The third aspect of the present invention provides a micro display device, comprising a working electrode, a luminescent pattern layer, a gel electrolyte layer and a counter electrode stacked in sequence; the luminescent pattern layer is formed by arranging the nano-pixel points provided by the first aspect of the present invention on the working electrode using an optical tweezers manipulation method.

[0035] Preferably, the material of the working electrode is selected from any one of a transparent indium tin oxide substrate, a transparent gold substrate, and a transparent fluorine-doped tin oxide.

[0036] Preferably, the gel electrolyte layer is prepared by mixing polyvinyl alcohol and hydrochloric acid.

[0037] Preferably, the method for preparing the micro display device comprises the following steps:

[0038] S1. Preparing patterned microelectrodes on a transparent substrate by maskless photolithography to obtain a transparent conductive substrate;

[0039] S2. Add the nano-pixel dots to deionized water and disperse them evenly. Use a pipette to draw a small amount of the dispersed liquid and drop it on a glass slide. Gently cover it with the transparent conductive substrate prepared in step S1 and place it on the sample stage of the optical tweezers system and fix it for later use.

[0040] S3. Turn on the illumination light of the optical tweezers system and adjust it to a suitable brightness. Move the sample stage in step S1 so that the sample is directly above the lens. Observe the sample through the eyepiece, adjust the focal length so that the 1064nm wavelength laser is focused on the transparent conductive substrate and the image is clearest, and find the position where the composite particles need to be patterned;

[0041] S4. Open the computer software of the optical tweezers system, adjust the corresponding L gear, so that the image is displayed on the computer screen, and fine-tune the focus to make the image clearest. Adjust the exposure time to achieve the best imaging effect on the screen, and calibrate the software to ensure that the captured particle is located in the center of the potential well;

[0042] S5. After the calibration is completed, click Manipulation Taps to set a new potential well, then import the specific pattern designed in advance into the Sequence, and then drag the pattern to the newly set potential well to obtain a multi-potential well pattern. Then use the mouse to control the position of the potential well, the switch, and the size of the potential well laser power. Turn on the laser and adjust it to the appropriate power. The particles are attracted to the center of the beam waist and move downward due to the gradient force pointing to the center of the beam waist and the downward scattering force. At the same time, adjust the focal length so that the focal plane is on the substrate surface. At this time, the particles contact the substrate surface. The adhesion force generated by the photothermal effect and the interaction force between molecules are used to fix the particles and then realize the patterning of multiple particles;

[0043] S6. After the particle patterning is completed, carefully take out the sample, remove the glass slide, blow off the excess suspension on the surface of the transparent conductive substrate with an ear-cleaning bulb, and dry it in a dry, dust-free environment to obtain a standby electrode;

[0044] S7. A layer of gel electrolyte is coated on the electrode, and another layer of blank conductive substrate is assembled into a sandwich structure device. Different voltages are applied to the device through an electrochemical workstation and the electrochemical performance is characterized. The pattern on the electrode changes color with the applied voltage. The optical properties of the nanopixels are characterized by a dark field optical microscope combined with a grating spectrometer.

[0045] Preferably, the exposure time in step S4 ranges from 0.065 to 49.9 ms.

[0046] Preferably, in step S5, the potential well laser power is about 0.05-0.1 W, and the potential well switching rate is 30-40 kHz.

[0047] Preferably, the preparation process of the gel electrolyte in step S6 comprises: preparing a 0.25 mol / L hydrochloric acid solution, adding polyvinyl alcohol (PVA) powder at a concentration of 0.1 g / mL, and magnetically stirring in a 95° C. water bath until the mixed solution becomes clear.

[0048] The beneficial effects of the present invention are as follows: Compared with the prior art, the present invention has the following effects:

[0049] 1. The present invention uses composite nanoparticles based on all-dielectric nanoparticles as nano-pixels for the first time, and then assembles them into various beautiful and orderly patterns in a controllable manner through optical tweezers assembly. It can be multi-channel regulated by electrochemical means, presenting vivid color dynamic switching, fast refresh speed, high contrast, low energy consumption, and no thermal effect.

[0050] 2. The nanopixels in the present invention can generate a unique coupled Mie resonance mode, and use electrochemical means to achieve efficient Fano resonance active tuning. By adjusting the carrier concentration of the electrochromic conductive polymer in the composite nanoparticles, the dielectric properties of the electrochromic conductive polymer can be changed to affect the electromagnetic dipole resonance of the all-dielectric nanoparticles, as well as the near-field and far-field coupling between the electrochromic conductive polymer and the all-dielectric nanoparticles. The unique electrochemical redox and electrochromic properties of the electrochromic conductive polymer help to achieve efficient active tuning of the optical response, avoiding the small tuning amplitude caused by the weak refractive index change of the single-component all-dielectric nanoparticle material during the carrier injection process. Combining this advantage of the electrochromic conductive polymer with the strong electromagnetic dipole resonance of the all-dielectric nanoparticles, the degree of freedom of regulation is increased, the tuning effect is good, and the tuning amplitude is larger than other electrical tuning methods.

[0051] 3. The present invention can control the concentration of the monomer and oxidant of the electrochromic conductive polymer during the preparation process, adjust the ratio of the electrochromic conductive polymer to the all-dielectric nanoparticles, change the optical response of the nano-pixel points, and achieve precise passive tuning to adjust the saturation and contrast of the micro-display device, thereby being suitable for different application scenarios.

[0052] 4. The present invention uses an optical tweezers system to precisely control the patterned arrangement of nano-pixels and regulates their optical response through electrochemical means. The prepared micro-display device is small in size and has potential application value in highly integrated optoelectronic regulation, display devices or high-density information encoding. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1 This is a dark field optical image of the nano-pixel point of Example 1 of the present invention.

[0054] Figure 2 This is a scanning electron microscope image of the nano-pixel points of Example 1 of the present invention.

[0055] Figure 3 Schematic diagram of manipulating nano-pixels in an optical tweezers system according to Embodiment 2 of the present invention.

[0056] Figure 4This is an optical image of the patterned nano-pixel array of Example 2 of the present invention.

[0057] Figure 5 This is a structural diagram of a micro display device according to Example 3 of the present invention.

[0058] Figure 6 1 and 2 are optical images of the patterned array of Example 3 of the present invention under different voltages.

[0059] Figure 7 This is a cyclic voltammetry curve of the micro display device of Example 3 of the present invention.

[0060] Figure 8 This is a scattering spectrum curve diagram of the nano-pixel point under different voltages in Example 3 of the present invention. DETAILED DESCRIPTION

[0061] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. The reagents or instruments used that do not indicate the manufacturer are all conventional products that can be purchased commercially.

[0062] The raw material information used in the embodiments of the present invention is as follows:

[0063] APTES, γ-aminopropyltriethoxysilane, chemically H2N(CH2)3Si(OC2H5)3.

[0064] SDS, sodium dodecyl sulfate, chemical formula: NaC 12 H 25 SO4.

[0065] APS, or ammonium persulfate, has a chemical formula of (NH4)2S2O8.

[0066] Example 1

[0067] The nano-pixel dots in this example are prepared by the following preparation method, specifically:

[0068] 0.1g of Si nanoparticle powder with a diameter of 100-200nm was added to 50mL of ethanol solvent, and after ultrasonication for 20min, magnetic stirring was continued for 30min to uniformly disperse the particles to obtain a dispersion. 24mL of 2mol / L ammonia solution was prepared and added dropwise to the dispersion, and stirred thoroughly to obtain a mixed solution. 4mL of γ-aminopropyltriethoxysilane (APTES) was added dropwise to the mixed solution, stirred for 2h, and the product was washed several times with deionized water and dried to obtain amino Si nanoparticles. 2mmol of the prepared amino Si nanoparticles was dispersed in 5mL of a mixed solution of sodium dodecyl sulfonate (SDS) and HCl, wherein the concentration of SDS was 0.5mmol / L and the concentration of HCl was 1mol / L, and magnetic stirring was performed to uniformly disperse the particles. Then, 0.02 mmol of aniline (Ani) monomer and 5 mg of ammonium persulfate (APS) powder were added in sequence, and magnetic stirring was continued at room temperature for 10 h. The product was washed three times with deionized water and dried to obtain core-shell structured pixels with polyaniline (PANI) as shell and Si nanoparticles as core (Si@PANI), i.e., nanopixels in this example. The optical microscope dark field image of the nanopixels in this example is shown in FIG. Figure 1 As shown in the scanning electron microscope image Figure 2 shown.

[0069] Example 2

[0070] The method for preparing the working electrode loaded with patterned nanoparticles in this example specifically comprises the following steps:

[0071] Patterned microelectrodes were prepared on a transparent substrate by maskless photolithography to obtain a transparent ITO substrate with microelectrodes. Si@PANI nanoparticles were added to deionized water, and magnetic stirring was performed after ultrasound to disperse the particles evenly. A small amount of the dispersed liquid was taken with a pipette and dropped on a glass slide, and the transparent ITO substrate was gently covered to obtain a sample to be processed. The sample to be processed was then placed on the sample stage of the optical tweezers system with the glass slide at the bottom and the transparent ITO substrate at the top and fixed. The bright field lens of the optical tweezers system was replaced with a dark field lens, and an objective lens with a numerical aperture of 0.7 was selected. The optical path of the system was adjusted to be located on the same straight line. After adjustment, the power button for controlling the illumination light was clicked in sequence, the power button for controlling the sample stage was clicked, the key to turn on the laser was turned on, and the computer was turned on after the laser was stable. The laser used was Gaussian light with a wavelength of 1064nm. Turn on the illumination light of the optical tweezers system, adjust it to a suitable brightness, and move the sample stage so that the sample is directly above the lens. Observe the sample through the eyepiece, adjust the focal length so that the laser is focused on the transparent ITO substrate and the imaging is clearest, and find the location where the composite particles need to be patterned.

[0072] Open the computer software of the optical tweezers system, adjust the corresponding L gear, so that the image is displayed on the computer screen, and fine-tune the focus to make the image clearest. Adjust the exposure time within the range of 20.0ms to achieve the best imaging effect on the screen. Create a new task (Project), then select Trap Calibration, and wait for the potential well to automatically capture particles for calibration to ensure that the captured nanopixel is located in the center of the potential well. After the calibration is completed, click Manipulation Taps to set a new potential well, and then import the pre-designed specific pattern into the sequence (Sequence), and then drag the pattern to the new potential well to obtain a multi-potential well pattern. Then use the mouse to control the position of the potential well, the switch, and the size of the potential well laser power. Turn on the laser and adjust it to the appropriate power, which is about 0.08W, and the potential well switching rate is 36kHz. The nanopixel will be subject to a gradient force pointing to the center of the beam waist and a downward scattering force. Under the action of these two forces, the nanopixel will be attracted to the center of the beam waist and move downward due to the scattering force. At the same time, the focal length is adjusted so that the focal plane is located on the substrate surface. At this time, the particles contact the substrate surface. The schematic diagram of manipulating nano-pixels in the optical tweezers system in this example is shown in FIG. Figure 3 As shown. The particles are fixed by the adhesion force generated by the photothermal effect and the interaction force between molecules. This process is repeated several times to achieve a patterned arrangement of multiple particles. After the particle patterning is completed, carefully take out the sample, remove the glass slide, and then use an ear bulb to blow away the excess suspension on the surface of the transparent ITO substrate. Dry it in a dry, dust-free environment to obtain a working electrode loaded with patterned nanoparticles. Observe its morphology under a dark field microscope. The optical image of the patterned array in this example is shown in Figure 4 shown.

[0073] Example 3

[0074] The present embodiment provides a method for preparing and controlling a microdisplay device based on optical tweezers manipulation. The specific implementation process is: prepare 5 mL of 0.25 mol / L hydrochloric acid solution, weigh 500 g of polyvinyl alcohol powder (PVA) and pour it into the solution, stir magnetically in a 95°C water bath until the mixed solution is clear, and prepare a gel electrolyte. A layer of gel electrolyte is coated on the patterned side of the working electrode loaded with patterned nanoparticles in Example 2, and then another blank transparent ITO substrate is covered on the electrolyte as a counter electrode to assemble into a transparent device with a sandwich structure. The working electrode and the counter electrode are respectively left with about half a centimeter of uncoated electrolyte, and are respectively connected to the working electrode clamp and the counter electrode-reference electrode clamp of the electrochemical workstation. Refer to the schematic diagram of the structure of the microdisplay device in this example. Figure 5 As shown, in Figure 5In the figure, 1 is the counter electrode, 2 is the gel electrolyte, 3 is the patterned particles, and 4 is the working electrode. Then different voltages (-2V, 0V, 2V) are applied to the above device, and the pattern on the electrode changes color with the applied voltage. The optical images of the patterned nano-pixel array under different voltages are shown in Figure 2. Figure 6 As shown, Figure 6 The voltages applied from top to bottom are -2V, 0V, and 2V. The above device is placed under the telephoto dark field objective (100x) of the microscope. Using a dark field optical microscope, the test object is located by observing the color of the light spots of different nano-pixels on the platform. The entire nanostructure is illuminated by oblique incident white light at an incident angle of 53° from above. After the power is turned on, a cyclic voltammetry test is set up using an electrochemical working method in combination with a grating spectrometer and a CCD camera. The cyclic voltammetry curve of the micro display device is shown in the figure below. Figure 7 As shown in Figure 1, as the scan rate increases, the basic shape of the curve does not change, and the peak current increases with the scan rate. The scattering spectra of the patterned nano-pixels in the working electrode at different voltages are characterized, and the scattering spectrum changes are shown in Figure 1. Figure 8 As shown in the figure, the finite difference time domain (FDTD) simulation is used to verify and analyze the regulation effect. It can be seen that the simulated change trend of the scattering spectrum of a specific nano-pixel at different voltages is consistent with the experimental results. When the voltage increases from -2V to 2V, the scattering intensity decreases. This is because when the voltage is changed, the carrier concentration of polyaniline changes, and the change in the redox state causes the dielectric constant and refractive index to change, thereby regulating the electromagnetic dipole resonance of the core all-dielectric nanoparticles (i.e., Si nanoparticles), and the resonant coupling between polyaniline and the core all-dielectric nanoparticles also changes accordingly.

[0075] In summary, the present invention uses all-dielectric nanoparticles coated with electrochromic conductive polymers as single-particle nanopixels for the first time, which overcomes the difficulty of nanosizing traditional pixels and avoids the problem of heat loss caused by plasmon metals as nanopixels. The nanopixels prepared by the composite of all-dielectric nanoparticles and electrochromic conductive polymers in the present invention produce a unique coupled Mie resonance mode, and use electrochemical means to achieve efficient Fano resonance active tuning. The refractive index of the all-dielectric material changes slightly during carrier injection, and the unique electrochemical redox and electrochromic properties of the electrochromic conductive polymer help to achieve efficient active tuning of the optical response. Combining this advantage of the electrochromic conductive polymer with the strong electromagnetic dipole resonance of the all-dielectric nanoparticles, the tuning effect is good, and the tuning amplitude is larger than other electrical tuning methods. The present invention is the first to controllably assemble nanopixels based on all-dielectric materials into various beautiful and optically attractive optical components by optical tweezers assembly. The pattern composed of nano-pixel points can be multi-channel regulated by electrochemical means, showing vivid color dynamic switching, fast refresh speed, high contrast, low energy consumption, and no thermal effect; the present invention can adjust the ratio of electrochromic conductive polymer to all-dielectric nanoparticles by controlling the concentration of monomers and oxidants in the process of preparing nano-pixel points, the core-shell structure can increase the degree of regulation freedom, and the optical response of nano-pixel points can be affected by changing the morphology and components, so as to achieve saturation and contrast regulation of the display device, and thus be suitable for different application occasions; the micro-display device prepared by the present invention is small in size and has potential application value in highly integrated optoelectronic regulation, display devices or high-density information coding.

[0076] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A nano pixel, characterized in that: The nano-pixel dots include composite nanoparticles with a core-shell structure, wherein the core of the composite nanoparticles is an amino-modified all-dielectric nanoparticle; the shell of the composite nanoparticles is an electrochromic conductive polymer; the all-dielectric nanoparticles include at least one of silicon nanoparticles, germanium nanoparticles, tellurium nanoparticles, and gallium arsenide nanoparticles.

2. The nano-pixel point according to claim 1, characterized in that: The electrochromic conductive polymer is selected from at least one of polyaniline, polypyrrole, polythiophene and polyacetylene.

3. The nano-pixel according to claim 1, characterized in that: The particle size of the nano pixel is 60 to 250 nm; And / or, the diameter of the all-medium nanoparticles is 50 to 200 nm.

4. The method for preparing nano-pixel dots according to any one of claims 1 to 3, characterized in that: The following steps are involved: The aminated all-medium nanoparticles are firstly mixed with a surfactant and an acid solution, and then mixed with a monomer of an electrochromic conductive polymer and an oxidant for reaction to obtain the nano pixel point.

5. The method for preparing nano-pixel dots according to claim 4, characterized in that: The preparation method of the aminated all-medium nanoparticles is to mix the all-medium nanoparticles with an ammonia solution, and then mix and react with γ-aminopropyltriethoxysilane to obtain the obtained nanoparticles.

6. The method for preparing nano-pixel dots according to claim 4, characterized in that: The molar ratio of the ammonia water to the all-medium nanoparticles is (10-36):1; And / or, the molar ratio of the γ-aminopropyltriethoxysilane to the all-medium nanoparticles is (3-10):

1.

7. The method for preparing nano-pixel dots according to claim 4, characterized in that: The oxidant comprises ammonium persulfate and / or potassium persulfate; And / or, the monomer of the electrochromic conductive polymer is selected from at least one of aniline, pyrrole and thiophene; and the surfactant includes dodecyl sulfonate.

8. The method for preparing nano-pixel dots according to claim 4, characterized in that: The molar ratio of the surfactant, the amino-modified all-medium nanoparticles and the acid solution is 1:(33-200):(83-250).

9. The method for preparing nano-pixel dots according to claim 4, characterized in that: The molar ratio of the amino-modified all-medium nanoparticles, the monomer of the electrochromic conductive polymer and the oxidant is (50-200):1:(0.5-3).

10. A micro display device, characterized in that: It comprises a working electrode, a luminescent pattern layer, a gel electrolyte layer and a counter electrode which are stacked in sequence; the luminescent pattern layer is formed by arranging the nano-pixel points described in any one of claims 1 to 3 on the working electrode using an optical tweezers manipulation method.